Advantages and disadvantages of endoscopically assisted front-lift - Dušková, Markéta; Kristen, M; Paděra, Jiří (Acta chirurgiae plasticae (English ed.), 2002)
Reduced surgical risk, a diminution of visible scars, rapid recovery, long-termed results and reduced costs are at present the most important demands on development in aesthetic plastic surgery. Endoscopically assisted frontlift meets perfectly the need of reduced invasivenes. It is technically simple and associated with a minimum of complications. It brings minimal scars beyond the hairline with a favourable effect after eliminating the drop of the brows, and wrinkles on the forehead. The duration of the effect in the aging face depends, however, similarly as other methods, on the characteristics of the skin, changes in other parts and the individua) disposition. A marked disadvantage is the high initial cost of special equipment. Their recovery ensues from the reduced time of surgery, reduced consumption of material, lower number of complications and more rapid return to norma) life.
Keywords: Patient Satisfaction; plastická chirurgie; dospělí; Adult; lidé; endoskopie; spokojenost pacientů; Middle Aged; obočí; lidé středního věku; ženské pohlaví; Female; Humans; Endoscopy; Eyebrows; Surgery, Plastic